Situation analysis for delivering integrated comprehensive sexual and reproductive health services in humanitarian crisis condition for Rohingya refugees in Cox’s Bazar, Bangladesh: protocol for a mixed-method study - Ahmed, Rushdia; Farnaz, Nadia; Aktar, Bachera; Hassan, Raafat; Shafique, Sharid Bin; Ray, Pushpita; Awal, Abdul; Rahman, Atiya; Urbaniak, Veronique; Kobeissi, Loulou Hassan; Rosie, Jeffries; Say, Lale; et al. (BMJ open, 2019)
IntroductionRohingya diaspora are one of the most vulnerable groups seeking refuge in camps of Cox’s Bazar, Bangladesh, arising an acute humanitarian crisis. More than half of the Rohingya refugees are women and adolescent girls requiring quality sexual and reproductive health (SRH) services. Minimum initial service package of SRH are being rendered in the refugee camps; however, WHO is aiming to provide integrated comprehensive SRH services to meet the unmet needs of this most vulnerable group. For sustainable and successful implementation of such comprehensive SRH service packages, a critical first step is to undertake a situation analysis and understand the current dimensions and capture the lessons learnt on their SRH-specific needs and implementation challenges. This situation analysis is pertinent in current humanitarian condition and will provide an overview of the needs, availability and delivery of SRH services for adolescent girls and women, barriers in accessing and providing those services in Rohingya refugee camps in Cox’s Bazar, Bangladesh, and similar humanitarian contexts.Methods and analysisA concurrent mixed-methods design will be used in this study. A community-based household survey coupled with facility assessments as well as qualitative in-depth interviews, key informant interviews and focus group discussions will be conducted with community people of Rohingya refugee camps and relevant stakeholders providing SRH services to Rohingya population in Cox’s Bazar, Bangladesh. Survey data will be analysed using univariate, bivariate and multivariable regression statistics. Descriptive analysis will be done for facility assessment and thematic analysis will be conducted with qualitative data.Ethics and disseminationEthical approval from Institutional Review Board of BRAC James P Grant School of Public Health (2018-017-IR) has been obtained. Findings from this research will be disseminated through presentations in local, national and international conferences, workshops, peer-reviewed publications, policy briefs and interactive project report.